Reforming international institutions: the domestic origins and conditional logic of governmental reform preferences1 - Finke, Daniel (International studies quarterly, 2013)
Governmental preferences are crucial to our understanding of European and international treaty reforms. Nevertheless, current research fails to explain why and under what circumstances governments prefer certain proposals for institutional reform. The present article analyzes the conditional nature of governmental reform preferences over different dimensions of institutional design. In doing so, it integrates endogenous and exogenous explanations for governmental reform preferences into a single theoretical framework. The longitudinal research design enables an explicit empirical analysis of the observed short-term changes in the governments' positions on European treaty reforms. In terms of political integration, these changes not only represent short-term trends in public opinion but also reflect the partisan composition of governments and parliaments. Both causal effects are mediated by the institutional design of the domestic preference aggregation process. With respect to institutional reforms, the governments' changing positions can be explained as a reaction to previous treaty reforms. Given a particular level of political integration, governments optimize the trade-off between decision-making power and efficiency. Hence, I find that preferences on political integration and institutional reform are conditional upon each other, with the direction and strength of this conditionality varying systematically across member states and changing over time.